Transforming Library and Higher Education Services in Support of Industrialization and Modernization - G. Kabatangare, Tumuhairwe (2019)
The major findings discovered throughout the research study were that the transformation and redefinition of academic library service in the higher education sector in support of industrialization and modernization is inevitable in order for the sector to stay relevant and that this critically hinges on functionalizing the productive involvement of Information Communication Technology (ICT) based digitalization of traditional higher education academic library service in the current global communication circuit of creation, organization, distribution, preservation and use of knowledge and information to efficiently meet current 21st century technologically and digitally inclined user needs. The objective of this paper was to examine the significance of ICT based digital transformation and redefinition of higher education academic library service in support of modernization and industrialization to staying relevant by meeting 21st century technologically and digitally inclined user needs. The research design was of a descriptive survey nature based on a critical analytical literature review methodology sourcing relevant purposively sampled literature from Library and Information Science (LIS) data bases and the world-wide-web for grey literature using a purposively selected higher education academic library service provider target population. The conclusion arrived at was that ICT based higher education academic library service digital transformation was a significant necessity for the service to stay relevant to 21st century modernized industrialized user needs